0617 Solriamfetol Treatment of Excessive Daytime Sleepiness in Parkinson's Disease: Results from a Phase 2 Proof-of-Concept Trial. (12th April 2019) - Schweitzer, Paula K; Hauser, Robert A; Amara, Amy W; Videnovic, Aleksandar; Comella, Cynthia; Liu, Kris; Sterkel, Amanda L; Gottwald, Mildred D; Steinerman, Joshua R; Jochelson, Philip; Emsellem, Helene
Abstract: Introduction: Excessive daytime sleepiness (EDS) is a debilitating non-motor symptom affecting patients with Parkinson's Disease (PD). Solriamfetol has demonstrated wake-promoting efficacy in clinical trials in narcolepsy and obstructive sleep apnea (OSA). Methods: This was a phase 2, double-blind, placebo-controlled, randomized, 4-week, crossover trial. Eligible participants were 35-80 years of age, diagnosed with mild to moderate idiopathic PD (UK PDS Brain Bank Criteria), with Epworth Sleepiness Scale (ESS) score >11. Participants were randomized (3:3:1) to receive one week of: A) placebo, solriamfetol 75mg, 150mg, and 300mg, B) solriamfetol 75mg, 150mg, 300mg, and placebo, or C) four weeks of placebo. Safety and tolerability were primary objectives and included assessment of adverse events. Efficacy endpoints were change from baseline in mean sleep latency on the Maintenance of Wakefulness Test (MWT) and ESS score. Results: Participants (n=66) were randomized (mean [SD] age, 64.6 [8.5]; 68.2% male) and n=62 completed the trial. At baseline, mean (SD) ESS score was 16.1 (2.9), and MWT sleep latency was 15.1 min (10.9). The most common treatment-emergent adverse events (≥5%) reported while taking solriamfetol were nausea (10.7%), dizziness (7.1%), dry mouth (7.1%), headache (7.1%), anxiety (5.4%), constipation (5.4%), and dyspepsia (5.4%). Least Square (LS) mean (SE) change from baseline in MWT (min) was 1.8 (1.9) for placebo, 0.4 (2.1) for 75mg (nominal p>0.05), 2.7 (2.2) for 150mg (nominal p>0.05), and 6.8 (2.1) for 300mg (nominal p=0.0098). LS mean (SE) change from baseline in ESS was -4.8 (0.6) for placebo, -4.8 (0.7) for 75mg, -5.0 (0.7) for 150mg and -5.7 (0.7) for 300mg; for change in ESS, all nominal p>0.05. Conclusion: The safety and tolerability of solriamfetol in PD was demonstrated; participants were able to safely titrate to 300mg, and adverse events were similar to narcolepsy and OSA trials. Solriamfetol treatment improved sleep latency on the MWT at 300mg but not at lower doses. While ESS improvement with solriamfetol was not different from placebo, the large placebo response, likely multifactorial in basis, may have confounded interpretation. Support (If Any): Jazz Pharmaceuticals